Effect of zinc and iron management with different level of nitrogen on growth and productivity of rice (Oryza sativa L.) under aerobic condition - Patel, Nirmala; Pramanik, Kalipada; Bhaduri, Debarati; Saren, Binoy Kumar (ORYZA-An International Journal of Rice, 2023)
A field experiment was conducted during kharif season of 2019 at Bhujabala, Rayagada (Odisha) and at the farmer's field, Lephripara, Sundargarh (Odisha) during kharif 2020, to study the effect of zinc and iron management on yield and yield attributes of aerobic rice with different level nitrogen fertilizer management. Experiment was laid out in Factorial Randomized Block-Design, treatments consisted of three levels of nitrogen management viz. N1-80 kg N ha-1, N2- 60 kg N ha-1 + 5 t FYM ha-1 and N3- 40 kg N ha-1 + 10 t FYM ha-1 and six micronutrient management, viz., M1 - Control, M2 - 0.5% zinc sulphate as foliar, M3 - 0.5% ferrous sulphate as foliar, M4 - 0.3% zinc sulphate as seed priming, M5 - 0.3% ferrous sulphate as seed priming, and M6 - 0.5% zinc sulphate as foliar + 0.5% ferrous sulphate as foliar. Results revealed that the application of 80 kg N ha-1, and 60 kg N ha-1 + 5 t FYM ha-1 recorded maximum growth parameters like plant height, number of tillers m-2, dry matter accumulation and leaf area index; higher yield attributes like number panicle m-2, number of filled grains panicles-1, fertility percentage and test weight. Combined application of 60 kg N ha-1 + 5 t FYM ha-1 recorded the maximum grain and straw yields. Results also showed that foliar application of 0.5% zinc sulphate as foliar + 0.5% ferrous sulphate as foliar exhibited higher growth parameters, yield attributes, grain and straw yield during the two years of experiment.